Il concetto di alienazione nell’ultima teoria critica - Vaccaro, Giovambattista (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2024)
The last generation of the Critical Theory of Society has discovered the notion of alienation again after a long oblivion since the end of the Sixties years. Its exponents use this notion as an analytic and critical tool of the pathologies in contemporary society and especially in the capitalistic one as a consequence of a wrong relation with the world and with ourselves. By this way they refer to the critical legacy of young Marx and the first generation of the Critical Theory. This article reconstructs this analysis and this criticism in the different authors of the new Critical Theory and shows some weaknesses of their argumentation and their proposals in front or the first Critical Theory of the old Frankfurt School. Alienation; Critical Theory; Honneth; Jaeggi; Rosa.